Digital Piracy: Factors on Using Software Piracy in Islamic Higher Education - Basrul; Zuhra Sofyan (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2023)
This research was conducted to identify and analyze the factors that lead to the use of pirated software among lecturers at UIN Ar-Raniry Banda Aceh and to determine the impact of using pirated software. The research method used is of quantitative type with factor analysis techniques. The study sample was 114 people. The sampling technique used is convenience sampling. The data was obtained through the distribution of questionnaires to respondents, which were further analyzed using the factor analysis method. The Kaiser Meyer Olkin Measure of Sampling test results were 0.801, and the Bartlett test was equal to 153. The next stage applies the principal component analysis method to obtain four new formation factors. They are named the motivation factor consisting of 9 variables; the attitude factor consisting of 4 variables; the legal factor consisting of 2 variables; and the quality & price factor consisting of 3 variables. The results achieved can be a reference and consideration for the campus in digital transformation using original software. The research implications contribute to a paradigm shift for lecturers to use licensed software. Socially, compliance with the regulation of the use of licensed software creates a favorable academic environment and has an impact on increasing lecturer productivity.